The measurement factor of employee participation for Knowledge Management System in engineering consulting firms - Tserng, H. Ping; Lee, Meng-Hsueh; Hsieh, Shang-Hsien; Liu, Hsiang-Ling (Journal of Civil Engineering and Management, 2016)
Knowledge Management Systems (KMS) is a fundamental tool in the implementation process of Knowledge Management (KM), which is used to manage knowledge of information technology systems in an organization. However, a well-developed KMS should not only take advantage of information technology function, but also require the development of a complete measurement system for KMS. The purpose of this research is to develop an employee participation framework to describe the cause-effect relationship of KMS. Three case studies were interviewed for building measurement factors of KMS used by engineering consulting firms. Two questionnaires were sent to managers of engineering consulting firms for establishing main factors and sub factors in the measurement system in which four primary objectives were identified as “Activity in forum”, “Statistic of knowledge system”, “Participation of KM activity”, and “Number of documents”. The cause-effect relationship among four objectives was shown by path analysis. First published online: 27 Aug 2015